Riba According to Sjafrudin Prawiranegara (1911 – 1989) and Muhammad Syafii Antonio (1967) (Critical Comparative Analysis of Islamic Legal Theory Perspective) - Faozi Latif (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2022)
Sjafrudin Prawiranegara and Syafii Antonio are two influential figures of Islamic economists in Indonesia. Both are considered to represent two different poles of Islamic economics. Sjafrudin represented critical thinking, while Syafii Antonio represented mainstream thinking. This paper was made with a theory approach istinbat} law. Based on an analysis with this approach, it was revealed that Sjafrudin Prawiranegara tended to interpret usury philosophically, while Syafii Antonio tended to emphasize more on the linguistic aspects (bayani) as the views of the main religious scholars. According to Syafrudin Riba is all the profits obtained based on transactions or agreements in which one party is abusing his strong economic position to take advantage that crosses the line from his weak counterpart. While Syafii Antonio equates usury with interest which means more than credit.